Hadith #4006 - Sahih Muslim - Sa'id bin Zayd (Sahih Muslim)
I heard Allah’s Apostle (ﷺ) say: He who took a span of earth wrongly would be made to wear around his neck seven earths on the Day of Resurrection.
Grade: Sahih

Hadith #5207 - Sahih Muslim - Sa'id bin Zayd (Sahih Muslim)
I heard Allah’s Messenger (ﷺ) as saying: Truffles are a kind of blessing and their juice is a medicine for the eyes. Shu’ba said: When Hakam narrated this hadith to me, I did not deem it as a Munkar hadith because of the narration of Abd al-Malik.
Grade: Sahih

Hadith #5209 - Sahih Muslim - Sa'id bin Zayd (Sahih Muslim)
Truffles are a kind of ‘Manna’ which Allah sent down upon Moses and their juice is a medicine for the eyes.
Grade: Sahih

Hadith #5210 - Sahih Muslim - Sa'id bin Zayd (Sahih Muslim)
Truffles are ‘Manna’ which Allah, the Exalted the Majestic, sent to the people of Israil, and its juice is a medicine for the eyes.
Grade: Sahih

Hadith #5211 - Sahih Muslim - Sa'id bin Zayd (Sahih Muslim)
Truffles are ‘Manna’ and its juice is the medicine for the eyes.
Grade: Sahih